The progress of pluripotent stem cell-derived pancreatic β-cells regeneration for diabetic therapy - Wang, Xin; Gao, Mengxi; Wang, Yali; Zhang, Yucheng (Frontiers in Endocrinology, 2022)
Diabetes is a complex metabolic disorder of carbohydrate metabolism, which is characterized by high blood glucose levels either due to an absolute deficiency of insulin secretion or an ineffective response of cells to insulin, a hormone synthetized by β-cells in the pancreas. Despite the current substantial progresses of new drugs and strategies to prevent and treat diabetes, we do not understand precisely the exact cause of the failure and impairment of β-cells. Therefore, there is an urgent need to find new methods to restore β-cells. In recent years, pluripotent stems cells (PSCs) such as embryonic stem cells (ESCs) and induced pluripotent stem cells (iPSC) can serve as an ideal alternative source for the pancreatic β-cells. In this review, we systematically summarize the current progresses and protocols of generation pancreatic β-cells from human PSCs; and finally discuss some of the challenges and future perspectives of human PSCs treatments for diabetes.